Perlindungan Hukum Terhadap Kekayaan Intelektual Dalam Era Digital Di Indonesia - Dian Utami Amalia; Bagos Budi Mulyana; Fajar Falah Ramadhan; Noerma Kurnia Fajarwati (Terang : Jurnal Kajian Ilmu Sosial, Politik dan Hukum, 2024)
The rapid development of digital technology has had a significant impact on the legal protection of intellectual property in Indonesia. In this digital era, intellectual property, such as copyrights, patents and brands, has become more vulnerable to infringement and misuse. This article reviews Indonesia's efforts to face these challenges by exploring the policies and regulations implemented to strengthen legal protection of intellectual property in the digital era. The Indonesian government has adopted various regulations that accommodate digital dynamics, such as revisions to copyright and patent laws. However, there are still challenges in effective implementation and enforcement of the law. This article also highlights collaboration between government, the private sector, and society in developing innovative solutions to improve intellectual property protection. By reviewing the latest legal and policy developments, this article provides a comprehensive picture of Indonesia's efforts to mitigate risks and increase protection of intellectual property in the digital era. In conclusion, strong and adaptive legal protection is very important to encourage innovation, investment and economic growth amidst the dynamics of the digital era.